PENERAPAN MEDIA PEMBELAJARAN PAPAN CERITA DALAM MENINGKATKAN MOTIVASI BELAJAR BAHASA INDONESIA - Risma Diah Juwanti; Uswatun Chasanah; Juhaeni Juhaeni; Lutfi Mushonif El Gufri (Universitas Negeri Makassar, 2026)
This study aimed to examine the increase in motivation to learn Indonesian using storyboards in grade IV at MIN 2 Sidoarjo. The method used is classroom action research with Kurt Lewin's approach, which is carried out in two parts, each involving planning, implementation, observation and reflection. The subjects of this study were 29 students, and the data collection instruments used were tests, observations, and questionnaires. The research data were analyzed using quantitative and descriptive techniques. This study found that students were much more motivated and performed better in their studies than before. The number of students who passed increased from 41% before the study to 62% in the first part and then to 83% in the second part. Observations also showed that students were more engaged, enthusiastic, willing to ask questions, and dedicated to completing their work than before. Therefore, storyboards are a good new way to make students more enthusiastic and improve their learning of Indonesian in elementary school.